HPLC analysis, antimicrobial and antioxidant activities of Daphne cneorum L. - Sovrlić Miroslav; Mandić Leka; Radojković Marija; Jusković Marina Ž.; Vasiljević Perica J.; Jelić Ratomir M.; Manojlović Nedeljko T.; Mašković Pavle Z. (Hemijska Industrija, 2012)
The present study describes in vitro antimicrobial and antioxidant activities of the methanol extracts which were obtained from the leaves and twigs of the plant Daphne cneorum L. The antimicrobial activity of these extracts was tested against human pathogenic microorganisms using a minimum inhibitory concentration (MIC) values. Total phenolics and flavonoids, as well as the antioxidant activity of the extracts were determined. The two tested extracts showed good antimicrobial and antioxidant activities. The results of a high performance liquid chromatographic (HPLC) method showed that 7,8-dihydroxycoumarin is one of the most abundant secondary metabolite in the tested extracts. The results of this study clearly indicated that the extracts of D. cneorum could be used as a potential source of natural antioxidant and antimicrobial agents.